Un tipus especial d’oracions interrogatives: les interrogatives escindides - Contreras, Joan M.; Roca, Francesc (Caplletra. Revista Internacional de Filologia, 2007)
This paper deals with the properties of interrogative sentences with a split constituent (or split interrogatives) in Catalan and Spanish. We compare split interrogatives with Wh-questions, yes/no questions, different kinds of confirmatory questions and clitic left dislocation constructions. Split interrogatives show a very clear-cut syntactic and phonological distinction between those constituents to be interpreted as shared or old information (theme) and the constituent which receives the focus of the sentence. Following recent theoretical work on the left periphery of the sentence, we propose that the Ground Phrase projection (placed below ForceP) is especially relevant in split interrogatives and that this relevance yields a derivation with two syntactic movements to the higher functional projections. Such analysis accounts for the surface constituent order found in split interrogatives, the semantic interpretation of each part of the sentence, and the syntactic structure of Wh-constituents, and it covers also several constraints on locality, syntactic distribution, definiteness, and negation that characterize split interrogatives.